Reduced Sodium Current in the Lateral Ventricular Wall Induces Inferolateral J-Waves - Meijborg, Veronique M. F.; Potse, Mark; Conrath, Chantal E.; Belterman, Charly N. W.; De Bakker, Jacques M. T.; Coronel, Ruben (Frontiers in Physiology, 2016)
Background: J-waves in inferolateral leads are associated with a higher risk for idiopathic ventricular fibrillation. We aimed to test potential mechanisms (depolarization or repolarization dependent) responsible for inferolateral J-waves. We hypothesized that inferolateral J-waves can be caused by regional delayed activation of myocardium that is activated late during normal conditions. Methods: Computer simulations were performed to evaluate how J-point elevation is influenced by reducing sodium current conductivity (GNa), increasing transient outward current conductivity (Gto), or cellular uncoupling in three predefined ventricular regions (lateral, anterior, or septal). Two pig hearts were Langendorff-perfused with selective perfusion with a sodium channel blocker of lateral or anterior/septal regions. Volume-conducted pseudo-electrocardiograms (ECG) were recorded to detect the presence of J-waves. Epicardial unipolar electrograms were simultaneously recorded to obtain activation times (AT). Results: Simulation data showed that conduction slowing, caused by reduced sodium current, in lateral, but not in other regions induced inferolateral J-waves. An increase in transient outward potassium current or cellular uncoupling in the lateral zone elicited slight J-point elevations which did not meet J-wave criteria. Additional conduction slowing in the entire heart attenuated J-waves and J-point elevations on the ECG, because of masking by the QRS. Experimental data confirmed that conduction slowing attributed to sodium channel blockade in the left lateral but not in the anterior/septal ventricular region induced inferolateral J-waves. J-waves coincided with the delayed activation. Conclusion: Reduced sodium current in the left lateral ventricular myocardium can cause inferolateral J-waves on the ECG.